Historical aspects of cardiovascular services in Nepal - Shah, Ram Kishor (Nepalese Heart Journal, 2000)
Himalayan Kingdom Nepal, birth place of Devi Sita, Lord Ram and Buddha is situated between two giant countries. The heart of Nepal is the beautiful flora and mighty Himalayas. Ayurveda was the main modality of therapy for most ancient Nepalese people. After the treaty of Sugauli in 1816 AD, a Residency office of British India was established in Kathmandu. Allopathic medical service was provided by the doctors posted in the residency. It was from that period the people in Kathmandu came to know about a system of medicine other than Ayurveda. After many years of this type of arrangement, Bir Hospital actually came into existence in 1889 AD, more than one hundred years ago.